The Safety and Innovation Effects of U.S. Liability Law: The Evidence - Litan, Robert E. (American Economic Review, 1991)
Although it has vanished from the front pages, the still continues to occupy the attention of policymakers, the business community, and consumers. Indeed, many states have responded to the crisis by enacting reforms to make it more difficult for accident victims to sue and, if they win, to recover large awards. Manufacturers and insurers have supported these efforts because they believe that the tort system has become so expensive and uncertain that is overdeterring, discouraging the production of valuable products and the of many more. Plaintiffs' lawyers and consumers groups vigorously disagree, arguing that current liability law provides important incentives for private actors to make safer products and to conduct their activities in a less risky fashion. Given the significant impacts of the tort system (by one recent estimate, gross liability expenditures in the United States amounted to $117 billion in 1987, see Tillinghast, 1989), it is somewhat surprising that there is so little empirical research to settle this debate. In fact, there even is a lack of consensus on liability trends. Although there are no comprehensive nationwide data on the numbers of nonautomobile tort suits, verdicts, and settlements, by all available measures, total liability costs (primarily insurance premiums, but also estimates of self-insurance payouts) have been rising during the last 30 years, and especially rapidly in the 1980's (U.S. Department of Justice, 1986; Mark Peterson; 1987). In 1989, the Brookings Institution launched a major study designed to determine the and innovation impacts of this expansion in the tort system on five sectors of the U.S. economy; the private aircraft, automobile, chemical and pharmaceutical industries, and the medical profession. As project directors, Peter Huber and I commissioned experts to address each side of the debate for each of these sectors, deliberately seeking individuals who were not economists. As discussed below, it is extremely difficult (some would say impossible) to establish through standard econometric techniques the linkages, if any, between liability law and safety and/or innovation. Accordingly, we believed the project could shed more light on the subject by engaging individuals with scientific or practical backgrounds in the specific sectors they were asked to study; in a few cases, economists met these criteria and they participated. This article summarizes some of the key findings from this effort (1991).